2016
DOI: 10.1177/0735633116656849
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Engagement of Students in Distance and Online Learning

Abstract: International audienceà veni

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 49 publications
9
64
0
3
Order By: Relevance
“…Because virtual communities also affect group identity, those network relations in social media of the friend-networking site type affect group identity and classroom group management in the online and offline classroom (Ho & Lin, 2016). Vayre and Vonthron (2017) showed that social support and social integration play an important role in student engagement with online learning environments and that loneliness is related to disengagement from such studies. When students feel lonely due to the lack of social interactivity online, they tend to finally drop their online course (El Said, 2016).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because virtual communities also affect group identity, those network relations in social media of the friend-networking site type affect group identity and classroom group management in the online and offline classroom (Ho & Lin, 2016). Vayre and Vonthron (2017) showed that social support and social integration play an important role in student engagement with online learning environments and that loneliness is related to disengagement from such studies. When students feel lonely due to the lack of social interactivity online, they tend to finally drop their online course (El Said, 2016).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…Schools should consider that using social networks might intensify lonely students’ feelings of frustration, because their expectations of being entertained and socially included may not be met. In particular, these teenagers may still feel lonely when communicating online in a social media learning environment, and loneliness may interfere with their academic engagement and performance in online courses (El Said, 2016; Vayre & Vonthron, 2017). For those students, a traditional face-to-face setting may be a more appropriate and gratifying approach.…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…In spite of the growing popularity of dual and jointly-taught degrees, research exploring students' views is limited, but a study conducted in Australia by Russell, Dolnicar and Ayoub (2008) showed how one of the main reasons for dissatisfaction was assessment incongruences and how ten years later this is still the main problem to tackle (Steel and Huggins, 2016). The distance learning aspect amplifies any issue arising in a jointly-taught degree, due to delayed or asynchronous feedback from and interaction with peers and instructors and a much more delicate and fragile sense of community than that oncampus students (Vayre & Vonthron, 2017). Hence, effective organisation and curriculum delivery of a jointly-taught programme require being proactive and fostering dialogue among all stakeholders involved (El-Mansour, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Capability attainment in online learning environments support a sense of belonging when students have greater awareness of their strengths within a curriculum, and social relations are established. Transition into a university is important in the student lifecycle and requires well-constructed orientation, teacher, and professional support linked to the psychological and sociological aspects of wellbeing (Vayre & Vonthron, 2016). First-generation university attendees may lack the cultural practices to successfully manage transition to higher education (Carroll-Meehan & Howells, 2018) with those beyond the transition period continuing to require human contact which may be lacking in fully online units of study.…”
Section: Early Meaningful Engagement and Sense Of Belongingmentioning
confidence: 99%